2010
DOI: 10.1111/j.1526-4610.2009.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of the Serotonin Transporter Gene in Migraine – An Association Study

Abstract: We report a case-control study with 251 unrelated migraine patients and 192 unrelated healthy controls to evaluate an association between the polymorphisms of the 5-HT transporter (5-HTT) gene rs2066713 and rs1979572 and different migraine phenotypes. We found a genetic association for the A allele of rs1979572 for migraine with aura (MA) especially in women as well as a significant lower prevalence for MA for carrier of the A allele of rs2066713 in women. These findings support previous results suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…In any case, rs2020942 is only one of the many SNPs located in the 5-HTT gene region, and the possibility of other SNPs in susceptibility to migraine cannot be ruled out. For example, one study, which was not included in the present meta-analysis because there was no similar study on the same SNPs available, found a genetic association between the A allele of rs1979572 and rs2066713 and MA, especially in women [49].…”
Section: Snp Rs2020942mentioning
confidence: 84%
“…In any case, rs2020942 is only one of the many SNPs located in the 5-HTT gene region, and the possibility of other SNPs in susceptibility to migraine cannot be ruled out. For example, one study, which was not included in the present meta-analysis because there was no similar study on the same SNPs available, found a genetic association between the A allele of rs1979572 and rs2066713 and MA, especially in women [49].…”
Section: Snp Rs2020942mentioning
confidence: 84%
“…Only few of the initial findings, however, were replicated, suggesting there may have been quite some false-positive results among them. Hence, in this review only a few examples of genetic association studies are given, also because testing for association with a focus on gender was rarely done.An example is a recent study, in which DNA variants of the serotonin 5-HT transporter gene, 5-HTT gene, were found to be associated with MA; 25 the authors claim a specific association of a 5-HTT allele in women, but one has to take into account that the overwhelming majority of the tested patients were of the female gender, which puts the finding in a rather different perspective as a possible association with the male gender could not be adequately investigated.Another example is the most often highlighted association with the MTHFR C677T polymorphism of the 5′,10′methylenetetrahydrofolate reductase (MTHFR) gene, which encodes a key enzyme in folate and homocysteine metabolism. 26 Although several studies found an association of the T-allele with MA, [27][28][29][30] there are also negative studies.…”
Section: Linkage and Candidate Gene Association Studies Of Migraine: mentioning
confidence: 99%
“…Serotonin binds to serotonin receptors, which comprise both metabotropic and ionotropic receptors. The two families of metabotropic serotonin receptors: 5HT 1 and 5HT 2 , have both been associated with migraine ( Hill and Reynolds, 2007 ; Ferrari et al , 2010 ; Nelson et al , 2010 ; Thompson et al , 2012 ; Yücel et al , 2016 ) as well as the serotonin transporter ( Ogilvie et al , 1998 ; Marziniak et al , 2005 ; Bayerer et al , 2010 ). We directly associate 5HT 2 with migraine in the visual cortex brown module as well as the G-protein-mediated signalling pathway including G o , which signals downstream of the 5HT 1 receptor.…”
Section: Discussionmentioning
confidence: 99%